1990
DOI: 10.1002/eji.1830200524
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of autoimmunity with H2 and T cell receptor β chain genotypesin (NZB x NZW) F2 mice

Abstract: Accelerated autoimmunity as expressed by the classical autoimmune strain mouse (NZB x NZW)F1 is thought to be the result of major histocompatibility complex (MHC)-associated NZW genes acting on a genetic predisposition for autoimmunity as expressed by the NZB mouse. To evaluate more accurately both H-2 and T cell receptor (TcR) beta chain involvement in F1 disease, we studied the segregation of NZB (H-2d, TcRB) and NZW (H-2z, TcRW) haplotypes of these genetic elements and the development of autoimmunity in (NZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, this does not imply that the Ea gene is the only gene encoded within MHC that determines the genetic susceptibility to murine SLE. Studies in New Zealand mice have demonstrated the association of the H-2 d/z heterozygosity or the bm12 mutation in the I-A␤ chain, independently of the expression of I-E molecules, with the development of SLE (27)(28)(29)(30). In view of particular sequence homologies of the A␤ ) failed to promote the development of SLE in (BALB.H-2 z ϫ NZB) ϫ NZB backcross mice (33).…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not imply that the Ea gene is the only gene encoded within MHC that determines the genetic susceptibility to murine SLE. Studies in New Zealand mice have demonstrated the association of the H-2 d/z heterozygosity or the bm12 mutation in the I-A␤ chain, independently of the expression of I-E molecules, with the development of SLE (27)(28)(29)(30). In view of particular sequence homologies of the A␤ ) failed to promote the development of SLE in (BALB.H-2 z ϫ NZB) ϫ NZB backcross mice (33).…”
Section: Discussionmentioning
confidence: 99%
“…While gross differences in immune function were not observed in these strains, functional consequences of these deletions have been reported. Some studies have concluded that the TCR deletions correlate with susceptibility or resistance to autoimmune diseases (27,28). Another study showed that deletions in TCR have an impact in specific immune responses (12).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies in New Zealand mice using (NZBxW)xNZB backcross, NZBXW E2, and H-2 congenic NZBXW mice by several groups have consistently demonstrated that the H-2''^^ hybrid MHC class II molecules produced in NZBxW mice are likely to act as restriction elements for their autoimmune disease (Hirose et al 1986, Kotzin & Palmer 1987, Noonan et al 1990). The role of hybrid class II molecules in the development of murine lupus was also suggested in studies on (NZWxBXSB)Ei and (NZWxSWR)Fi hybrid mice (Kawano et al 1992, Ghatak et al 1987.…”
Section: I-a Association Of Murine Sle and Its Abrogation By The Yaa mentioning
confidence: 99%